Integration of the Republic of Lithuania into the European Union in the Context of the Union of Lublin: Constitutional Aspects - Sadzevičius, Martynas; Višnevskaja, Viktorija (Vilnius University Open Series, 2024)
When we see the processes of globalisation taking place at the present time, and when we associate Lithuania’s integration primarily with integration into the European Union, we completely forget about the processes that took place in the 17th century when the Grand Duchy of Lithuania and the Kingdom of Poland formed a common federal aristocratic monarchy. Looking back in time and observing a certain regularity, we can apply the knowledge gained from the analysis to assess the current processes of Lithuania’s integration into the European Union, which have taken place very recently and are still ongoing, and which is a valuable experience for us in anticipating possible challenges. The research work analyses the integration processes and the differences between the integration of the Grand Duchy of Lithuania in the Republic of the Two Nations in the context of the Lublin Union of 1569 and the integration of the Republic of Lithuania after its accession to the European Union. This theme is explored through the constitutional aspects, the changes in integration in general, the impact on the symbols of statehood - the currency, the coat of arms, the flag, the capital, and the status of the language, as well as the aspects of autonomy in the administration of justice and the regulation of customs. Integration in itself is not necessarily a process that diminishes the importance of national symbols, and this is well illustrated by the status of the language, but reverse changes, such as changes in the currency, are not excluded.